Author Correction: An open data infrastructure for the study of anthropogenic hazards linked to georesource exploitation - Orlecka-Sikora, Beata; Lasocki, Stanisław; Kocot, Joanna; Szepieniec, Tomasz; Grasso, Jean Robert; Garcia-Aristizabal, Alexander; Schaming, Marc; Urban, Paweł; Jones, Glenda; Stimpson, Ian; Dineva, Savka; Sałek, Piotr; et al. (Scientific data, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.